Insurance networks outside the village and social network analysis: Evidence from rural Malawi - Westland, Clifford Gerrit (Université d'Ottawa | University of Ottawa, 2015)
The development literature has consistently overlooked out of village links in the evaluation of informal insurance networks. This paper provides evidence that such an oversight may give a flawed impression of network formation decisions, given the high proportion of non-local transfer links in most studies to date – almost 60% in the Malawian data used for this study. Using a series of OLS and probit regressions, the results of this paper point to an endogenous propensity for households to link with non-local individuals for their informal insurance networks in a manner that distinguishes them from within-village insurance links.